Analisis Sistem Manajemen Pergudangan Pada Pt. Liquid Kencana Abadi - Waruwu, Rizka Amanah Suryani; Bate’e, Maria Magdalena; Lase, Heseziduhu; Gea, Jeliswan Berkat Iman Jaya (LPPM Universitas HKBP Nommensen, 2024)
A warehouse is a separate area that functions as a place to store raw materials, parts and supplies. Every warehouse cannot be separated from a system. Warehouse Management System which is a warehouse management system that regulates/controls all warehouse activities, as is done by PT information. Liquid Kencana Abadi, a company engaged in the sale and distribution of goods. The objectives of this research are 1) To find out the warehouse management system at PT. Liquid Kencana Abadi, 2) To find out the problems faced by PT. Liquid Kencana Abadi in terms of warehouse management systems, and 3) To find out efforts to overcome warehouse management system problems at PT. Liquid Kencana Abadi. The type of research used is a descriptive qualitative approach method. Based on the known results of research conducted by researchers, they can find out the implementation of the warehouse management system implemented at PT. Liquid Kencana Abadi cannot yet be implemented optimally, this can be seen through the process of ordering and storing goods which is still not carried out effectively and efficiently. Furthermore, in this research it can be seen that the problems faced in implementing the warehouse management system are internal obstacles, such as human error problems and a less conducive warehouse environment. The efforts that have been made by PT. Liquid Kencana Abadi in overcoming this problem is by re-evaluating the warehouse management system process that has been carried out.